Assembly of aligned semiconducting carbon nanotubes in organic solvents via introducing inter-tube electrostatic repulsion. (May 2019) - Gao, Bing; Zhang, Xiaopin; Qiu, Song; Jin, Hehua; Song, Qijun; Li, Qingwen
Abstract: The main challenge for application of solution-derived carbon nanotube (CNT) in high performance field-effect transistor is how to obtain the aligned film with full surface coverage and uniform inter-tube pitch. Herein, a wafer-scale aligned array of s-SWCNTs can be assembled using the combination of the introduced inter-tube electrostatic repulsion and an improved "bi-phasic" dip-coating method. By using a conjugated molecule with positive charge to modify the charge on the surface of s-SWCNTs dispersed in organic solvents, the inter-tube electrostatic repulsion was correspondingly introduced. The inter-tube electrostatic repulsion can significantly inhibit the agglomeration of s-SWCNTs in the formation process of the aligned SWCNT films. Significantly, the aligned SWCNT thin film exhibits excellent surface coverage and anisotropy over the 3 inch aligned area. Graphical abstract: Image 1